Study of the [lambda]-[lambda] interaction with femtoscopy correlations in pp and p-Pb collisions at the LHC - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Klewin, Sebastian; Köhler, Markus Konrad; Leardini, Lucia; Ohlson, Alice; et al. (Physics letters, 2019)
This work presents new constraints on the existence and the binding energy of a possible Λ-Λ bound state, the H-dibaryon, derived from Λ-Λ femtoscopic measurements by the ALICE collaboration. The results are obtained from a new measurement using the femtoscopy technique in Image 1 collisions at s=13 TeV and p-Pb collisions at sNN=5.02 TeV, combined with previously published results from Image 1 collisions at s=7 TeV. The Λ-Λ scattering parameter space, spanned by the inverse scattering length f0−1 and the effective range d0, is constrained by comparing the measured Λ-Λ correlation function with calculations obtained within the Lednický model. The data are compatible with hypernuclei results and lattice computations, both predicting a shallow attractive interaction, and permit to test different theoretical approaches describing the Λ-Λ interaction. The region in the (f0−1,d0) plane which would accommodate a Λ-Λ bound state is substantially restricted compared to previous studies. The binding energy of the possible Λ-Λ bound state is estimated within an effective-range expansion approach and is found to be BΛΛ=3.2−2.4+1.6(stat)−1.0+1.8(syst) MeV.